THE EFFECT OF PROJECT BASED LEARNING AND STUDENTS’ PERCEIVED LEARNING DISCIPLINE TOWARD THE WRITING COMPETENCY OF THE ELEVENTH GRADE STUDENTS OF SMAN 5 MATARAM IN THE ACADEMIC YEAR 2012/2013 - Chikita, G.P.; Padmadewi, Ni Nyoman; Suarnajaya, I Wayan (Jurnal Pendidikan Bahasa Inggris Indonesia, 2013)
ABSTRACT This experimental study aims at investigating the effect of Project Based Learning (PBL) and students? perceived learning discipline on students? writing competency of the eleventh grade students of SMAN 5 Mataram. PBL is a teaching method which underlies on project given to the students. Besides teaching method, learning discipline is taken into account because it is predicted can affect the students? achievement in learning foreign language. This research involved three type variables, namely: teaching method as independent variable, learning discipline as moderator variable, and students? writing competency as dependent variable. To conduct this research, 80 students were selected as the sample. The design of this research was 2x2 factorial design. Data were collected by an instrument called posttest which is essay type test. The acquired data were analyzed statistically by two way ANOVA. This research discovers: 1) there is a significant effect of PBL on students? writing competency, 2) there is no significant effect of the interaction between teaching methods (PBL and conventional teaching method) and students? learning discipline level (high and low levels) on students? writing competency, 3) PBL has significant effect for both high and low discipline students. Based on the analysis, PBL has positive effect on students? writing competency. So, it is recommended to apply this teaching method in writing class as an alternative way to improve students? writing competency.Key words: project based learning, learning discipline, writing competency